Comparison Between Corporate Philanthropy and Corporate Strategy toward Market Valuation - Limbunan, Excel; Ng, Suwandi; Asri, Marselinus (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study aims to analyze the comparative impact of corporate philanthropy and corporate strategy in mediating the influence of corporate governance on market valuation. Design/methodology/approach – This study is based on the resource-based view theory and stakeholder theory. This study uses secondary data in the form of financial reports and annual reports obtained from the IDX database and the company's official website. The sample selection used the purposive sampling method. Findings – The results of this study indicate that there is a significant effect on the relationship between corporate governance and corporate strategy, the relationship between corporate strategy and market valuation. In addition, there is a significant effect of corporate governance on corporate philanthropy, and corporate philanthropy on market valuation. As well as an insignificant effect between corporate governance and market valuation. Originality/value - The population in this study were all non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Keywords: Corporate Governance, Corporate Philanthropy, Corporate Strategy, Market Valuation Paper type Research Result